The relationship between left ventricular dilation and right ventricular diastolic function in children with a patent ductus arteriosus - Cole Miller; William Anderson; Joseph A Paolillo; Matthew C Schwartz (Wolters Kluwer Medknow Publications, 2023)
The impact of a dilated left ventricular (LV) on right ventricular (RV) diastolic function has not been investigated. We hypothesized that in patients with a patent ductus arteriosus (PDA), LV dilation causes elevation of the RV end-diastolic pressure (RVEDP) through ventricular-ventricular interaction. We identified patients' ages 6 months to 18 years who underwent transcatheter PDA closure at our center from 2010 to 2019. One hundred and thirteen patients were included with a median age of 3 years (0.5-18). The median LV end-diastolic dimension (LVEDD) Z-score was 1.6 (−1.4-6.3). RVEDP was positively associated with RV systolic pressure (0.38, P < 0.01), ratio of pulmonary artery/aortic systolic pressure (0.4, P < 0.01), and pulmonary capillary wedge pressure (0.71, P < 0.01). RVEDP was not associated with LVEDD Z-score (0.03, P = 0.74). In children with a PDA, RVEDP was not associated with LV dilation, but was positively associated with RV systolic pressure.